The Impact of Recent Crises on Kazakhstan‘s Mining Industry - Koraus, Antonin; Schagerl, Christopher; Gombar, Miroslav; Jancikova, Eva (Journal of Ecohumanism, 2024)
The mining and quarrying industry is one of the main pillars of Kazakhstan’s economy. According to the National Bank of Kazakhstan (2023), the industry accounts for about 15% of the country's GDP. Kazakhstan is source of 1.8% of the world’s oil reserves. From FDI-perspective the EU is the largest investment partner. As a member of the Eurasian Economic Union dominated by the Russian Federation, Russia is also the major trading partner. On the other hand, the country has close ties with China as many transportation routes of the extractive East towards the consuming West pass-through Kazakhstan. In times of the COVID-19 crisis, the Russian-Ukrainian conflict and the intense focus on the dependence on natural resources and diversification of the supply portfolio, Kazakhstan has recently attracted increased international attention. The mining industry also faces the risk of additional sanctions from the EU and the USA. This article focuses on the impact of the recent crises on the mining industry of Kazakhstan. The source for the research on the mining industry is the country’s foreign trade and foreign direct investment data. It also provides a forecast based on the country’s strategy for the development of the mining industry in the coming years.